Chapter Some new results on gaps between consecutive primes - János Pintz (De Gruyter, 2013)
The paper presents a brief history of results about small gaps between con¬secutive primes and mentions some recent results of the author, in some cases only with a sketch of the main ideas, in some cases with detailed proofs